2013
DOI: 10.1182/blood-2012-05-432203
|View full text |Cite
|
Sign up to set email alerts
|

Improving overall survival and overcoming adverse prognosis in the treatment of cytogenetically high-risk multiple myeloma

Abstract: Multiple myeloma (MM) is a heterogeneous disease with certain genetic features [eg, t(4;14), del17p] associated with worse outcome. The introduction of thalidomide, lenalidomide, and bortezomib has dramatically improved the outlook for patients with MM, but their relative benefit (or harm) for different genetic patient subgroups remains unclear. Unfortunately, the small number of patients in each subgroup frequently limits the analysis of high-risk patients enrolled in clinical trials. Strategies that result i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
123
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(132 citation statements)
references
References 61 publications
6
123
0
3
Order By: Relevance
“…Other authors have previously shown the negative impact of high-risk abnormalities, such as t(4;14), t(14;16), t(14;20) and del17p, on survival outcomes in patients with newly diagnosed MM. 26,27 Similar findings were demonstrated in patients receiving front-line ASCT, in which high-risk cytogenetics was associated with worse outcomes 28 and unsustained CR at one year. 29 The prognostic impact of adverse cytogenetics on alloSCT outcome in MM is not well established.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Other authors have previously shown the negative impact of high-risk abnormalities, such as t(4;14), t(14;16), t(14;20) and del17p, on survival outcomes in patients with newly diagnosed MM. 26,27 Similar findings were demonstrated in patients receiving front-line ASCT, in which high-risk cytogenetics was associated with worse outcomes 28 and unsustained CR at one year. 29 The prognostic impact of adverse cytogenetics on alloSCT outcome in MM is not well established.…”
Section: Discussionsupporting
confidence: 68%
“…haematologica | 2016; 101(9) tions, 27 a recent study on UCBT 19 showed no association between high-risk cytogenetic and poor outcomes. A possible explanation for these findings might be the different risk group classification of patients harboring del13q.…”
mentioning
confidence: 99%
“…[16][17][18][19] Bortezomib has been combined with other MM drugs leading to several highly effective combination regimens. [11][12][13][14][15]20 In particular, bortezomib plays a critical role in the management of patients with genetically high-risk MM 14,[21][22][23] and patients with renal insufficiency. 24,25 The introduction of subcutaneous administration has improved convenience compared with the intravenous approach and substantially reduced the risk of peripheral neuropathy (PN), 26 a major limiting factor for long-term administration.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Although the precise molecular events that generate MM remain incompletely understood, our understanding of events that underlie its development have greatly advanced. 18 Moreover, patients' response to bortezomib-based regimens is highly variable, and drug resistance inevitably emerges even in patients who initially responded. The incidence and prevalence of MM are steadily rising in Western countries because of an aging population combined with the increased overall survival of patients with MM.…”
mentioning
confidence: 99%